2020
DOI: 10.3390/pharmaceutics12100914
|View full text |Cite
|
Sign up to set email alerts
|

Praziquantel–Clays as Accelerated Release Systems to Enhance the Low Solubility of the Drug

Abstract: Praziquantel is an antiparasitic drug indicated for the treatment of the schistosomiasis disease. This drug has very low aqueous solubility, requiring high oral doses for its administration which gives rise to side effects, therapeutic noncompliance and the appearance of resistant forms of the parasite. Clay minerals, like sepiolite and montmorillonite, are innocuous, non-toxic, biocompatible and low-cost excipients. Additionally, clays have high adsorbent properties that allow them to encapsulate drugs in nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…When dissolved in the solvent, the drug can be easily absorbed by halloysite nanotubes with continuous stirring and vacuuming. Borrego-Sánchez et al studied its interaction with low aqueous soluble antiparasitic drugs with the other clay materials [ 2 , 25 ]. One hundred and fifty milligrams of permethrin (Sigma Aldrich, St. Louis, MO, USA) was dissolved in 3 mL of 95% ethanol (Sigma Aldrich) to obtain a saturated solution (50 mg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…When dissolved in the solvent, the drug can be easily absorbed by halloysite nanotubes with continuous stirring and vacuuming. Borrego-Sánchez et al studied its interaction with low aqueous soluble antiparasitic drugs with the other clay materials [ 2 , 25 ]. One hundred and fifty milligrams of permethrin (Sigma Aldrich, St. Louis, MO, USA) was dissolved in 3 mL of 95% ethanol (Sigma Aldrich) to obtain a saturated solution (50 mg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Ana Borrego-Sánchez et al also studied a drug with low water solubility—praziquantel—for which the dissolution rate is a factor that limits bioavailability. The team obtained praziquantel–clay and praziquantel–calcium carbonate systems, successfully achieving accelerated release and increased solubility for the drug [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoclays are good candidates to be used as vehicles of melatonin because of their widely known capabilities for the retention of organic molecules, and protecting the loaded actives from degradation and improving their release profiles once administered [26][27][28][29]. Nanoclays are well known ingredients of skin formulations [30] once they have accomplished safety and stability requirements [31].…”
Section: Introductionmentioning
confidence: 99%
“…The drug intercalated into montmorillonite interlayer and the hybrid was even more effective as antibacterial that the pristine drug. Montmorillonite, laminar mineral, can be used to modify the release of drugs [29,42], and to protect them from the degradation [43]. Moreover, it have been recently demonstrated that clays have a proliferative effect on fibroblasts [44], which can lead to a potential synergistic effect between melatonin and montmorillonite for wound heling and skin protection.…”
Section: Introductionmentioning
confidence: 99%